2017
DOI: 10.1016/j.semcdb.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle docking at the cellular port: Extracellular vesicle binding and uptake

Abstract: Extracellular vesicles (EVs), lipid bilayer-enclosed structures that contain a variety of biological molecules shed by cells, are increasingly becoming appreciated as a major form of cell-to-cell communication. Indeed, EVs have been shown to play important roles in several physiological processes, as well as diseases such as cancer. EVs dock on to the surfaces of recipient cells where they transmit signals from the cell surface and/or transfer their contents into cells to elicit functional responses. EV dockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
189
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(204 citation statements)
references
References 100 publications
2
189
0
1
Order By: Relevance
“…Bone marrow macrophages from SA mice were not deficient in phagocytosis compared with WT macrophages ( Figure S4A). Fortuitously, we also observed that IFN suppressed the uptake of empty protein-less liposomes (Figure S4B), suggesting an inhibitory effect of IFN on lipid membrane fusion, which is involved in many types of TEV uptake (French et al, 2017).…”
Section: Ifn-induced Ch25h Limits Uptake Of Tev and Interrupts The Edmentioning
confidence: 57%
See 1 more Smart Citation
“…Bone marrow macrophages from SA mice were not deficient in phagocytosis compared with WT macrophages ( Figure S4A). Fortuitously, we also observed that IFN suppressed the uptake of empty protein-less liposomes (Figure S4B), suggesting an inhibitory effect of IFN on lipid membrane fusion, which is involved in many types of TEV uptake (French et al, 2017).…”
Section: Ifn-induced Ch25h Limits Uptake Of Tev and Interrupts The Edmentioning
confidence: 57%
“…Uptake of extracellular vesicles can occur through a number of mechanisms, including phagocytosis, endocytosis, micropinocytosis, direct membrane fusion, etc. (French et al, 2017). Bone marrow macrophages from SA mice were not deficient in phagocytosis compared with WT macrophages ( Figure S4A).…”
Section: Ifn-induced Ch25h Limits Uptake Of Tev and Interrupts The Edmentioning
confidence: 94%
“…The expelled EVs may interact with the ECM and be recognized by parental (autocrine) or other (paracrine) recipient cells for which they act as guidance or regulatory inputs, for instance during collective directional cell migration . EVs may also interact directly with cellular surfaces and exert their effect on contact, or undergo different forms of internalization (phagocytosis, macropinocytosis, endocytosis, or fusion) . Such uptake may either be nonproductive and result in degradation of the EV cargo, e.g., by phagocytes, or such cargo may be incorporated into recipient cells changing their properties .…”
Section: Functional Properties Of Extracellular Vesicles In Cancermentioning
confidence: 99%
“…Modes of MV cargo uptake by recipient cells include simple plasma membrane-EV fusion with direct cargo deposition into the cytoplasm, and the uptake of intact vesicles via multiple mechanisms for trafficking to an endosomal or lysosomal compartment. [82][83][84] EV uptake by recipient cells is carried out by a variety of modes, including clathrin and caveolin-mediated endocytosis, 85 lipid raft endocytosis, 86,87 phagocytosis 83 and micropinocytosis, 85,88 likely guided by vesicle membrane composition and surface protein profile. 83 Further, low pH as provided by tumor microenvironments would be conducive to the fusion of MV membranes with recipient cells.…”
Section: Uptake Of Evs Into Cellsmentioning
confidence: 99%